Electroacupuncture for Bladder Function Recovery in Patients Undergoing Spinal Anesthesia. (23rd December 2014) - Gao, Yinqiu; Zhou, Xinyao; Dong, Xichen; Jia, Qing; Xie, Shen; Pang, Ran
Abstract : Purpose . To determine the efficacy of electroacupuncture on recovering postanesthetic bladder function. Materials and Methods . Sixty-one patients undergoing spinal anaesthesia were recruited and allocated into electroacupuncture or control group randomly. Patients in electroacupuncture group received electroacupuncture therapy whereas ones in control group were not given any intervention. Primary endpoint was incidence of bladder overdistension and postoperative urinary retention. Secondary endpoints included time to spontaneous micturition, voided volume, and adverse events. Results . All patients (31 in electroacupuncture group and 30 in control group) completed the evaluation. During postoperative follow-up, patients in electroacupuncture group presented a significant lower proportion of bladder overdistension than counterparts in control group (16.1% versus 53.3%, P < 0.01). However, no significant difference was found in incidence of postoperative urinary retention between the two groups (0% versus 6.7%, P > 0.05). Furthermore, a shorter time to spontaneous micturition was found in electroacupuncture group compared to control group (228 min versus 313 min, P < 0.001), whereas urine volume and adverse events had no significant difference between the two groups. Conclusions . Electroacupuncture reduced the proportion of bladder overdistension and shortened the time to spontaneous micturition in patients undergoing spinal anesthesia. Electroacupuncture may be a therapeutic strategy for postanesthetic bladder dysfunction.